A new species of Hapalogenys (Lobotiformes: Lobotidae) from the Western Indian Ocean - Bogorodsky, Sergey V.; Matiku, Patroba; Reddy, Seshnee (Zootaxa, 2026)
A new species of grunter, Hapalogenys olivaceus, is described based on two specimens trawled during a survey conducted by the research vessel Dr. Fridtjof Nansen from off Tanzania in 2023, representing the first record of the genus from the Western Indian Ocean. Phylogenetic analysis of the COI barcoding region revealed that the species is a member of the H. kishinouyei species complex, the known members of which are characterized by the presence of two to five longitudinal stripes on the body. However, Hapalogenys olivaceus sp. nov. differs from species of this complex by having a uniformly olive-brown head and body and a pale area posterior to the pectoral fins. In addition, the new species can be distinguished from all eight congeners by the following combination of characters: dorsal-fin rays XI,14; pored lateral-lines scales 44–45; nasal pore followed by a series of distinct pores along the ventral margin of the suborbital; suborbital deeply notched; maxilla scaly; relatively short soft rays in dorsal and anal fins; first pelvic-fin ray filamentous; and black membranes in the posterior portion of the spinous dorsal fin.